Understanding the world economy - Cleaver, Tony; ebrary, Inc. (London : Routledge, 2002)
The world economy is constantly changing and developing. This new edition of Understanding the World Economy has been fully revised and updated to take account of current developments in this fascinating area of economics.
Includes index.
Previous ed.: 1997.
oif 22/07/16
Loans
Keywords: Economic development; International trade; Environmental economics; Debts, External; Foreign exchange